Peningkatan Kemampuan Motorik Halus pada Anak Melalui Permainan Membuat Plastisin Alami - Maftuhah Maftuhah; Endang Ratnasari (Universitas Trunojoyo Madura, 2014)
The ability of the child’s motor skills to achieve optimal results will not growup. So if it is not learned, the ability to improve the child’s motor is very low. To overcome this problem, in this case carried out research to improve fine motor through the creation of a natural clay using action research. This study involved children aged 4-5 years in RA Darul Ulum Bogobabadan Karangbinangun Lamongan. This study examines how the implemention of the game makes a natural clay and hw to improve fine motor skills of children through the game makes a natural clay. Besides that, also needed to develop the creativity of the child so that the child’s intellectual children more confident about what they are doing. This research was conducted in two cycles. One cycle consists of two activities that mix and knead the dough and make free creations of dough platisin. The results of the cycle there is still a failure of both these activities, children are still many who received a three star rating (good) is only 16,66 %. While in the second cycle of the two activities the children who received three-star rating (good) achieve the assessment criteria above average, reaching 63,33%, of the assessment criteria of at least 60,00%. Therefore this research has achieved success in improving fine motor.